Systematic Literature Review and Future Agenda: Leadership Style and Dimension in Rural Tourism Settings - Kusumawardhani, Yuviani (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
This article aims to outline research developments regarding leadership styles in rural tourism and a leadership measurement index to explore future research direction opportunities. A systematic literature review was conducted by reviewing a total final sample of 15 articles published from 2012-2021; the database sources used in the study were Elsevier, Emerald, MDPI, Taylor and Francais, and Harzing's Publish or Perish with the Scopus API Key based on inclusion and exclusion criteria for analysis and synthesis to meet the purpose of the article. Leadership styles in rural tourism are currently found in 14 leadership styles. All leadership styles in rural tourism illustrate the need for integration and networks to develop successful rural tourism, in contrast to the leadership styles adopted by other sectors. The dimension of leadership measurement in rural tourism is based on the rural tourism characteristics. There are twelve leadership dimensions measurement in rural tourism that are different from the measurement of leadership in general. There are theoretical and empirical gaps, so one of the challenges in applying the dimensions of leadership measurement is bridging research with applications in other sectors. This literature review is presented to describe the leadership style in rural tourism that is needed and has been widely adopted to help and support the community to find a successful leadership style in developing rural tourism.